Pengaruh Media Belajar Situs Web Carrd.Co Terhadap Keterampilan Menulis Berpadu Budaya Betawi - Mutiara Halimatu's Sadiyah; Khaerunnisa (Yayasan Al-Afif, 2025)
In this study, the problem found was the low short story writing skills of students in grade XI of SMA Triguna Utama. The low ability to write short stories can be caused by internal and external factors. In internal factors, the lack of imagination possessed by students can hinder story writing. Then for external factors, learning media as a tool to project learning materials can affect the stability of student learning. Therefore, this study applies the carrd.co website media as a tool to improve students' short story writing skills. Not only helping with the material, this media also introduces the history of Betawi culture to students. The research method used is quantitative research with a quasi-experimental research design. Based on the results of the research that has been tested, the application of the carrd.co website media in the experimental class and the control class has quite significant differences. Thus, the carrd.co website media is effective for use as a learning medium.